Analysis of the anti-cancer activity of novel indigenous algal compounds in breast cancer: towards the development of a model for screening anti-cancer stem cell activity - Lawson, Jessica Clair (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2010)
Breast cancer, the most common malignancy diagnosed in women, is one of the leading causes of death in women worldwide. In South Africa only 32% of women diagnosed with advanced breast cancer survive more than five years. The search for new chemotherapeutic agents capable of effectively treating breast cancer is therefore essential. Recent evidence supporting the cancer stem cell theory of cancer development for breast cancer challenges the current theories of cancer development and hence treatment. Cancer stem cells are a small subpopulation of tumour cells that possess properties of both cancer cells and stem cells and are believed to be the tumour-initiating population of many cancers. Cancer stem cells are inherently resistant to many chemotherapeutic agents and in this way have been associated with repopulation of tumours after chemotherapy. This phenomenon is proposed as a possible mechanism for cancer relapse after treatment. Cancer stem cells have also been implicated in metastasis, the major cause of mortality in cancer patients. Therefore, any treatment that is capable of targeting and removing breast cancer stem cells may have the theoretical potential to effectively treat breast cancer. However, there are currently no such treatments available for clinical use. We were provided access to a library of novel indigenous small molecules isolated from red and brown algae found off the Eastern Cape of South Africa. The aim of this project was to analyse the anti-cancer and anti-cancer stem cell properties of the compounds in this library and to identify hit"Ÿ compounds which could form the basis for future development into new anti-cancer drugs. Ten novel compounds of algal origin were tested for cytotoxicity, by determining their ability to inhibit the growth of MCF12A breast epithelial cells and MCF7 breast cancer cells using the colorimetric MTT [(3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] cell proliferation assay. All but one of the compounds tested exhibited cytotoxicity towards the MCF7 cancer cell line, with IC50 values (the concentration of the compound that leads to a 50% inhibition in cell growth) of between 3 Î¼M and 90 Î¼M. The chemotherapeutic drug paclitaxel was used as a positive control. Four of the compounds (RUMB-001, RUMB-002, RUMB-007 and RUMB-010/saragaquinoic acid) were significantly more toxic to the MCF7 cancer cell line, than the normal"Ÿ MCF12A breast cells and were selected as priority compounds for further analyses. In addition, two other compounds were selected as priority compounds, one highly cytotoxic towards both MCF12A and MCF7 cell lines (RUMB-015) and one which was non toxic to either cell line (RUMB-017/018). Preliminary studies into the mechanism of cytotoxicity using Western blot analysis for poly (ADP-ribose) polymerase (PARP) cleavage and Hoechst 33342 immunostaining in MCF-7 cells were largely unsuccessful. The Hoechst 33342 immunostaining assay did provide tentative evidence that selected priority compounds were capable of inducing apoptosis, although these assays will need to be repeated using a less subjective assay to confirm the results. The priority compounds were subsequently investigated for their cytotoxic effect on the cancer stem cell-enriched side population in MCF7 cells. The ability of the priority compounds to selectively target the cancer stem cell containing side population was assessed using two complementary flow cytometry-based techniques "“ namely the Hoechst 33342-exclusion assay, and fluorescent immunostaining for the expression of the putative cancer stem cell marker, ABCG2+. The ABCG2+ staining assay was a novel technique developed during the course of this study. It remains to be fully validated, but it may provide a new and reliable way to identify and analyse cancer stem cell containing side population cells. The MCF7 cells were treated with the compounds and the proportion of putative cancer stem cells compared with the size of the population in untreated cells was assessed. Three compounds (RUMB-010, RUMB-015 and RUMB-017/018) capable of reducing the proportion of side population cells within the MCF7 cell line were identified. Taking these data together, we identified two potential hit"Ÿ compounds which should be prioritised for future research. These are compounds RUMB-010/sargaquinoic acid and RUMB-017/018. RUMB-010 is of interest as it was shown to target the putative cancer stem cell population, in addition to the bulk MCF7 tumour line, but was relatively less toxic to the normal"Ÿ MCF12A cell line. RUMB-017/018 is of interest due to the ability to selectively target the cancer stem cell enriched side population, while having little effect on the normal (MCF12A) or bulk tumour (MCF7) cell lines tested. These compounds will be important as hit"Ÿ compounds for drug development and as tool compounds to study cancer and cancer stem cell biology.
Keywords: Breast -- Cancer; Breast -- Cancer -- Chemotherapy; Breast -- Cancer -- Treatment; Red algae; Brown algae; Algae -- Biotechnology